COVID-19 Knowledge and Pandemic-Associated Distress Among the Hospital Pharmacist Workforce in China. (25th November 2023) - Yang, Dongliang; Ma, Xueying; Fu, Songnian; Zhao, Jun; Aierken, Aizezijiang; Teng, Liang; Gao, Xiaoli
Abstract: Background: The unprecedented disruption brought about by the global coronavirus disease 2019 (COVID-19) pandemic had produced tremendous influence on the practice of pharmacy. Sufficient knowledge of pharmacists was needed to deal with the epidemic situation; however, outbreak also aggravated psychological distress among health-care professionals. Therefore, this study aimed to determine knowledge about the pandemic and related factors, prevalence and factors associated with psychological distress among hospital pharmacists of Xinjiang Province, China. Methods: An anonymous online questionnaire-based cross-sectional study was conducted by means of WeChat, a popular social media platform in China, February 23-27, 2020, during the COVID-19 outbreak. The survey questionnaire consisted of 4 parts, including informed consent section, demographic section, knowledge about COVID-19, and assessment of overall mental health through World Health Organization's Self-Reporting Questionnaire (SRQ-20). A score of 8 or above on SRQ-20 was used as cutoff to classify the participant as in psychological distress. SRQ-20 score and related knowledge score were used as dependent variables, demographic characteristics (such as gender, age, monthly income, etc.) were used as independent variables, and univariate binary logistic regression was used to screen out the variables with P < 0.05. Then, the filtered variables were used as independent variables, and multivariate logistic regression models were used to analyze associations with sufficient knowledge of COVID-19 and psychological distress. Results: A total of 365 pharmacists participated in the survey, fewer than half (35.1%; n = 128) of pharmacists attained a score of 6 or greater (out of 10) in overall disease knowledge, and most were able to select effective disinfectants and isolation or discharge criteria. In the multivariable model, age ages 31-40 (odds ratio [OR] = 3.25; P < 0.05), ages 41-50 (OR = 2.96; P < 0.05) versus >50 (referent); primary place of practice in hospitals: drug supply (OR = 4.00; P < 0.01), inpatient pharmacy (OR = 2.06, P < 0.01), clinical pharmacy (OR = 2.17, P < 0.05) versus outpatient pharmacy (referent); monthly income Renminbi (RMB, China's legal currency) 5000-10, 000 (OR = 1.77; P < 0.05) versus < 5000 (referent); contact with COVID-19 patients or suspected cases (OR = 2.27; P < 0.01); access to COVID-19 knowledge remote work+ on-site work (OR = 6.07; P < 0.05), single on-site work (OR = 6.90; P < 0.01) versus remote work (referent) were related to better knowledge of COVID-19. Research found that 18.4% of pharmacists surveyed met the SRQ-20 threshold for distress. Self-reported history of mental illness (OR = 3.56; P < 0.05) and working and living in hospital versus delay in work resumption (OR = 2.87; P < 0.01) were found to be risk factors of psychological distress. Conclusions: Further training of COVID-19 knowledge was required for pharmacists. As specific pharmacist groups were prone to psychological distress, it was important for individual hospitals and government to consider and identify pharmacists' needs and take steps to meet their needs with regard to pandemic and other work-related distress.